(untitled) (Journal of Asian Development Studies, 2025)
Knowledge is a strategic factor which provides a competitive advantage in a fierce competition environment. Sustainability of organization, which can be affected by various factors, is needed to transfer of strategic and specialized knowledge from executive to other managers and workers. But the transfer of knowledge is a complicated process, because the knowledge has cognitive or subjective traits as well as objective framework. Because of the nature of knowledge, there are some classifications about its traits. Tacit knowledge and explicit knowledge are the most common classification which emphasizes tacit knowledge is so embedded in the individual while explicit is about facts and things. From this point of view, the aim of this study is to examine the relationship between the behavior of knowledge transfer and properties of middle level manager. The sample group consists of 335 middle level managers in public enterprises in Turkey. The data were collected through a questionnaire that is reformed by the authors as 10 items with reference to Bock et al. (2005) and Göksel et al. (2010). As a result of the conducted analysis, statistical significant relationships were found between the two variables (p<0,01). Finally, demographic information of the sample is seen important for researchers, professionals, and those interested in these fields.